Nigeria’s Financial Sector Development and Crude Oil Exports: Is There a Link? - Ogunjumo, Rotimi Ayoade; Folorunso, Benjamin Ayodele; Ibitowa, Stephen Adesina; Onabote, Ademola Andrew (International Journal of Energy Economics and Policy, 2023)
Using yearly data from 1986 to 2020, the study looked at whether the Nigeria's financial sector development is connected to the country’s ever increasing crude oil exports. The results of the utilized Autoregressive Distributed Lag (ARDL) model demonstrated that, both in the short and long periods, there is no connection between Nigeria's financial sector development and crude oil exports. Additionally, the research indicated that the country's financial system is not yet adequately established to sustain exports of goods other than crude oil in the short term.